Sector paper on rural development (Staff working paper, 1988)
"As part of the self-appraisal of strategy in this field, initiated in 1984 by Dr. S.C. Jha, Manager AED, two seminars were held, one on rural development (1984) and another on rural employment creation (1986). This Staff Working Paper prepared under the direction of Dr. Jha and assisted by Dr. Martin C. Evans (Staff Consultant), reflects the deliberations of the seminars, views of the concerned departments and comments by staff. It is hoped that this paper will be useful for the Bank staff to reappraise the concept of rural development and design future projects that would systematically address rural poverty."--Foreword.